Olanzapine vs. magnesium valproate vs. lamotrigine in anti-N-methyl-D-aspartic acid receptor encephalitis: a retrospective study - Yinhua Yan; Chenxiao Yao; Bo Zhang; Zhenyu Yang; Jiahui Xie; Miao Tang; Qiong Long; Ewen Tu; Xuanqi Dong (BMC Neurology, 2024)
Abstract Background This study aimed to compare the impact of olanzapine, magnesium valproate, and lamotrigine as adjunctive treatments for anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. And it is expected to add supporting points related to the rebalance of neurotransmitters in the brain through adjuvant therapy in the clinical management of anti-NMDAR encephalitis. Methods This retrospective study included patients diagnosed with anti-NMDAR encephalitis who received standardized immunotherapy at Hunan Brain Hospital between January 2018 and December 2020. Results Compared to the olanzapine group, both the magnesium valproate and lamotrigine groups showed lower scores on the positive and negative symptom scale (PANSS) total score after 3 weeks of treatment (all P < 0.05). The Montreal Cognitive Assessment Scale (MoCA) scores in the magnesium valproate and lamotrigine groups were significantly higher than in the olanzapine group after 3 weeks and 3 months of treatment (all P < 0.05). After 3 months of treatment, the proportions of patients with a modified Rankin scale score (mRS) of 0–1 in the magnesium valproate and lamotrigine groups were significantly higher than in the olanzapine group (all P < 0.05). The electroencephalogram (EEG) abnormality ranks at 3 months were significantly lower in the magnesium valproate and lamotrigine groups compared with the olanzapine group (all P < 0.05). Furthermore, the Glx/Cr ratio significantly decreased after 3 months of treatment (all P < 0.05) in the magnesium valproate and lamotrigine groups, while the Glx/Cr ratio in the olanzapine group showed no significant change (P > 0.05). Conclusion Compared with olanzapine, the addition of magnesium valproate or lamotrigine to immunotherapy might be associated with a lower PANSS score, higher MoCA score, and lower mRS score. The improvement of neurological functions and cognitive function may be related to the decreased Glx/Cr ratio.